Genomic damage as a biomarker of chronic kidney disease status. (19th September 2014) - Corredor, Zuray; Stoyanova, Elitsa; Rodríguez‐Ribera, Lara; Coll, Elisabet; Silva, Irene; Diaz, Juan Manuel; Ballarin, José; Marcos, Ricard; Pastor, Susana
Abstract : Patients suffering from chronic kidney disease (CKD) exhibit a high incidence of cancer and cardiovascular diseases, as well as high levels of genomic damage. To confirm the association of CKD with genomic damage we have carried out the largest study to date addressing this issue, using a total of 602 subjects (187 controls, 206 pre‐dialysis CKD patients and 209 CKD patients in hemodialysis). DNA oxidative damage was measured in all individuals using the comet assay. Our results indicate that CKD patients have significantly higher levels of DNA damage than controls, but no significant differences were observed between pre‐hemodialysis (pre‐HD) and hemodialysis (HD) patients. When oxidative damage was measured, no differences were observed between patients and controls, although HD patients showed significantly higher levels of oxidative damage than pre‐HD patients. In addition, a positive relationship was demonstrated between genomic damage and all‐cause mortality. Our study confirms that genomic damage can be predictive of prognosis in CKD patients, with high levels of DNA damage indicating a poor prognosis in HD patients. Environ. Mol. Mutagen. 56:301–312, 2015. © 2014 Wiley Periodicals, Inc.